Radical emotionalism as a meta-metaethical position - Hartman, Jan (Hybris, 2021)
This paper attempts to develop a theoretical perspective which combines ethics and metaethics jointly with their links to the rational plots of the living moral reality. The author claims that the nature of morality is strictly emotional and criticizes false attempts to rationalize moral sphere, in many cases resulting from the ideas and arguments produced by the academic ethics or metaethics and subsequently infiltrating the social life. Imposed by the very theoretical nature of philosophy, intellectualism of the theoretical developments in ethics has a wrongful effect for public morals, falsifying the emotional nature of morality and providing individuals with false and rhapsodic, pseudo-theoretical topoi of contention, justifying and assessment. The article may be read as fundamentally undermining ethics as a historically influential moral as well as theoretical enterprise (with exclusion of the emotionalist tradition).